EFEKTIVITAS SUPERVISI AKADEMIK BERBASIS DIGITAL DALAM MENINGKATKAN KINERJA GURU DI ERA KURIKULUM MERDEKA - Shelvia, Bet (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2025)
This study aims to analyze the effectiveness of digital-based academic supervision in improving teacher performance in the era of the Merdeka Curriculum at SMA Negeri 3 Palangka Raya. This research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, involving principals and teachers as the main subjects. The data were analyzed using an interactive model, which includes data reduction, data display, and conclusion drawing and verification. Data validity was ensured through triangulation and member checking. The results show that digital academic supervision facilitates performance monitoring, accelerates feedback delivery, and encourages continuous teacher self-reflection. Teachers generally responded positively to digital supervision, considering it flexible, transparent, and supportive of professional development. This supervision also had a significant impact on improving teachers' ability to design differentiated learning tools and formative assessments aligned with the Merdeka Curriculum. Nevertheless, challenges such as limited digital literacy and technology access remain obstacles to be addressed. Therefore, infrastructure support and adaptive school leadership are essential to ensure the successful implementation of digital-based academic supervision.